'Ungentlemanly capitalism': John Hay and Malaya, 1904–1964. Issue 1 (2nd January 2019) - White, Nicholas J.
ABSTRACT: John Hay was one of Britain's leading colonial capitalists, building his career from the 1900s to the 1960s in Malaya's plantation industry. He became the leading spokesperson for the British rubber growers, and played a major role in the formulation of international restriction schemes during the 1930s. Hay was a remarkable entrepreneurial talent, consolidating his corporate power through the premiere Malayan agency house, Guthrie & Co. This in itself challenges the notion that Britain's myriad of 'free-standing' companies, which were typical of direct investment in the Empire, represented a relatively weak and unsustainable form of multinational enterprise. But Hay's dominance of the Malayan plantation sector also questions the notion of 'gentlemanly capitalism' as the driving force behind the expansion and sustenance of the British imperial system. Hay's network of colonial corporate influence did not extend into the corridors of 'gentlemanly capitalist' power in Whitehall and the City, where he often had frosty relations. Ultimately, it was the financial sector in London that brought about Hay's forced resignation from Guthrie in 1963. Examining questions of class, ethnicity, personality, ideology and strategy, the article focuses on why Hay did not develop better relations with commercial, financial and official elites, issues that would also engender tensions with the post-colonial political and business leadership of Malaya/Malaysia.